The Optical Investigation on Initial Flame Developing Characteristics of Diesel Jet under Cold Start Conditions. Issue 10 (27th July 2021) - Wu, Han; Zhang, Lu; Li, Haiying; Ma, Yupo; Liu, Fushui
ABSTRACT: Cold start ability is essential for heavy duty vehicles equipped diesel engine operating in cold regions. However, it is the diesel jet's initial flame developing characteristics that determines whether it is able to start success. Thus, it is investigated on a constant volume chamber by optical diagnostics technologies. In order to simulate cold start conditions, there are four conditions varied during experiments including injection pressure (40 160 MPa), ambient temperature (707 K 827 K), ambient density (9.1 22.6 kg/m 3 ), and fuel temperature (343 K 283 K). It is found that under low ambient temperatures flame starts as blue color then turning to yellow to realize high-rate heat release. And, a bimodal phenomenon on flame intensity is found during ignition process which can be used as transition indicator between two flames. With the reduction of the ambient temperature and density, the ignition delay and ignition position increase and finally misfired. At the low ambient temperature of 723 K, increasing injection pressure is unconducive to stabilize initial flame, which means that the higher injection pressure might not helpful for cold start. Moreover, the ignition delay decreased from 1.7 to 1.1 ms when fuel temperature increased from 283 to 343 K at the ambient temperature of 808 K, which indicates fuel heating is a promising way to improve diesel engine cold start.